Analisis Perbandingan Kinerja Investasi Perbankan Syariah dan Konvensional di Indonesia - Nayla Putri Hasibuan; Paisal Rahmat; Risky Hamonangan; Purnama Zein Nasution (Ekonomi, Keuangan, Investasi dan Syariah (EKUITAS), 2026)
nvestment performance is an important indicator in assessing the efficiency, effectiveness, and profitability of banking institutions, especially in comparing conventional and sharia systems that have different operational characteristics. This comparative quantitative research aims to analyze and compare the investment performance of conventional and sharia banking in Indonesia using Bank Rakyat Indonesia (BRI) and Bank Syariah Indonesia (BSI) as representatives of each system. Investment performance is evaluated through Return on Assets (ROA) and Return on Equity (ROE) indicators. This study uses quarterly financial report data for the 2020–2025 period obtained from official bank reports and publications of the Financial Services Authority (OJK). Data analysis techniques include descriptive statistics, normality tests, and hypothesis testing using the Independent Sample t-Test with SPSS. The results show that the average ROA and ROE values ​​of conventional banks tend to be higher than those of sharia banks. However, the Independent Sample t-Test produces a Sig. (2-tailed) value of 0.896 for ROA and 0.914 for ROE. Since this value is greater than the 0.05 significance level, it is concluded that there is no statistically significant difference between the investment performance of Islamic banking and conventional banking. This finding indicates that both banking systems have comparable capabilities in generating profitability and managing investments. The contribution of this study lies in providing the latest empirical evidence regarding the comparative investment performance of BSI and BRI post-merger during the 2020–2025 period, thereby enriching the literature on the competitiveness of Islamic and conventional banking and providing a reference for investors and bank management in making investment decisions and business strategies.